EVALUASI RENCANA KERJA DAN ANGGARAN PUSAT PENGELOLAAN BARANG MILIK NEGARA KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL DENGAN PENDEKATAN MODEL LOGIKA (LOGIC MODEL) - , Gumilar Achmad R; , Prof. Dr. Gudono, MBA., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discusses about work plan evaluation and budget using logic model in one of unit eselon 2 of Ministry of Energy and Mineral Resources, Center of Management Assets. It is expected that this research can show the relationship between work plan and the budget in achieving the vision and mission of the organisation. Besides, it is expected that this research can provide a recomendation for the leader in taking policy that's related to the progress of Centerof Management Assets, Ministry of Energy and Mineral Resources. The research is conducted by analyzing data and confirming it with questionaire and interview. The technique used is qualitative analysis. Generally, the ideal work plan and budget has not been achieved, even thought it is been supported by the related policies. There are several obstacles in work plan and budget such as : 1) the presence of several interventions in budget allocation in budget study by the DPR-RI